Penerapan Metode Discovery Learning Berbasis Media Film Pendek dalam Pembelajaran Menulis Cerpen pada Siswa Kelas IX SMP Negeri 2 Bunobogu Tahun Pelajaran 2024/2025: Penelitian - Wafik Ativa; Asna Ntelu; Puspita Dian Agustin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the planning, implementation, assessment, and to describe the factors and solutions to overcome the inhibiting factors in the implementation of the Discovery Learning method based on short film media in learning to write short stories for class IX students of SMP Negeri 2 Bunobogu in the 2024/2025 Academic Year. The method used in this study is a descriptive method with a qualitative research type. The data used in this study are notes on student activities during learning, and the results of students' short stories, as well as the results of photo documentation. The data sources in this study are data obtained directly from the research subjects, namely the results of interviews with teachers and students of SMP Negeri 2 Bunobogu, the results of observations of the learning process in class, and short story writing tests carried out by students. Data collection techniques are carried out by means of observation, interviews and documentation. Data analysis techniques in this study are carried out through the stages of data reduction, data presentation and drawing conclusions. Discovery Learning with short films is effective for teaching short story writing in grade IX of SMPN 2 Bunobogu in 2024/2025, and the obstacles can be overcome with the right strategy.